Chapter Storytelling and Other Skills: Building Employability in Higher Education - Boffo, Vanna (Studies on Adult Learning and Education, 2020)
The storytelling device introduces the search for our roots, as persons and human beings. To write an autobiography is to seek our roots not only through retrospection, interpretation, and creation but through an act of profound freedom towards ourselves. To tell our story is to put back together the pieces of our existence and, in doing so, to rebuild it. Recounting our work, at a certain point in our professional life, is like putting it back at the centre of our lives, it is like giving meaning to our actions, and starting to understand and interpret them again. This is why it is so important to recount our work, both for the narrator and the listener. From this point, we are trying to put in front of the educational perspectives the narration of the self as a central point of reflection on the knowledge, competences, and capabilities for entering into the world of work with responsibility, awareness, and a deep sense of citizenship. Following these indications, we thought that it could be a useful exercise to reflect on professionals' stories in order to look inside the self. At the same time, we trust it is very important for young adults transitioning into the world of work.